Examining the policy climate for HIV prevention in the Caribbean tourism sector : a qualitative study of policy makers in the Dominican Republic - Padilla, M. B. [et al] (2012)
Investigates the policy barriers and resources for HIV prevention in the tourism sector in the Dominican Republic. Concludes that the environment is ready for dialogue between the public-private sector to in order to develop regulatory mechanisms, joint responsibilities and centralised funding sources to ensure a sustainable response to the HIV-tourism linkage.